A method and system for road pavement life cycle cost analysis - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2017)
The present invention relates generally to a life cycle cost analysis. It relates more particularly to a method and system to process the cost data to be used as inputs for road pavement life cycle cost analysis.